Pituitary Macrotumor Causing Narcolepsy‐Cataplexy in a Dachshund. (15th January 2017) - Schmid, S.; Hodshon, A.; Olin, S.; Pfeiffer, I.; Hecht, S.
Abstract : Familial narcolepsy secondary to breed‐specific mutations in the hypocretin receptor 2 gene and sporadic narcolepsy associated with hypocretin ligand deficiencies occur in dogs. In this report, a pituitary mass is described as a unique cause of narcolepsy‐cataplexy in a dog. A 6‐year‐old male neutered Dachshund had presented for acute onset of feeding‐induced cataplexy and was found to have a pituitary macrotumor on magnetic resonance imaging (MRI). Cerebral spinal fluid hypocretin‐1 levels were normal, indicating that tumor effect on the ventral lateral nucleus of the hypothalamus was not the cause of the dog's narcolepsy‐cataplexy. The dog was also negative for the hypocretin receptor 2 gene mutation associated with narcolepsy in Dachshunds, ruling out familial narcolepsy. The Dachshund underwent stereotactic radiotherapy (SRT), which resulted in reduction in the mass and coincident resolution of the cataplectic attacks. Nine months after SRT, the dog developed clinical hyperadrenocorticism, which was successfully managed with trilostane. These findings suggest that disruptions in downstream signaling of hypocretin secondary to an intracranial mass effect might result in narcolepsy‐cataplexy in dogs and that brain MRI should be strongly considered in sporadic cases of narcolepsy‐cataplexy.